(untitled) (Sustainability in Debate, 2023)
Climate adaptation tends to face resistance or produce adverse effects, if it is tested only on the generalist scientific models, ignoring its effects on the culture, values, and worldviews of local communities. This article investigates how climate change has threatened the livelihood and cultural dimensions of peri-urban communities in the Central Amazon. The analysis is based on the cultural theory of risk in climate adaptation and its relationships to local Ecosystem Services (ES). In this case study, semi-structured interviews were conducted with residents of three municipalities in the Metropolitan Area of Manaus-Brazil. Given that their diet used to be heavily based on native food, the results show how Amazonian communities are adapting their eating habits in response to climate and environmental changes to the ES decline in the category of food security (i.e., in the class of provisioning ES). In addition, these services have relevant cultural value (i.e., cultural services). The ES reduction influences adaptation strategies amid the dismantling of current environmental policies. As a result, these communities began to adopt industrialized means of production and consumption, such as adopting products derived from cattle, whose production is the main cause of greenhouse gas emissions in Brazil. Therefore, the studied case demonstrates how climate adaptation may pressure and erode local cultures, when these following the logic of globalized urbanization.